NON-INVASIVE MONITORING OF FOETAL ANAEMIA IN KELL SENSITIZED PREGNANCY - Nisa, Zaibun; Sheikh, Sana Sadiq (Journal of Ayub Medical College Abbottabad, 2015)
We report a case of Kell sensitized pregnancy with good neonatal outcome. Anti-K antibodies were detected in maternal serum in early pregnancy as a part of routine antibody screening test. The middle cerebral artery doppler monitoring and serial titers were carried out to screen for foetal anaemia. Despite of rising antibody titers, serial middle cerebral artery doppler was normal and did not showed foetal anaemia. The pregnancy was carried out till term and patient delivered at 37 weeks of pregnancy with no evidence of foetal anaemia. This case underlines the need of general screening on rare antibodies in all pregnant women and that non-invasive monitoring of foetal anaemia can be done with anti-k titers and middle cerebral artery Doppler. Keywords: Kell, Blood group incompatibility, Irregular antibodies, Noninvasive monitoring